2007
DOI: 10.2495/wrm070291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preozonation and prechlorination on total organic carbon removal in surface water treatment in Iran

Abstract: In drinking water treatment, prechlorination and preozonation are often applied in order to control micro-organisms and taste and odour causing materials, which may influence organics removal by pre-oxidation and adsorption.Using commercial and natural water humid substances, the positive effect of prechlorination and preozonation as an aid to coagulation-flocculation of these compounds were confirmed by the removal of total organic carbon (TOC). These experiments were conducted at bench-scale through a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Torabian et al evaluated the effect of pre-ozonation on the TOC removal in surface water treatment. The results showed that pre-ozonation not only supplied the required material to remove TOC, but also improved TOC removal (24). Generally, with increasing ozone dosage at different coagulant dosages slightly, TOC removal increased but at average coagulant dosages, it was decreased (25).…”
Section: Introductionmentioning
confidence: 92%
“…Torabian et al evaluated the effect of pre-ozonation on the TOC removal in surface water treatment. The results showed that pre-ozonation not only supplied the required material to remove TOC, but also improved TOC removal (24). Generally, with increasing ozone dosage at different coagulant dosages slightly, TOC removal increased but at average coagulant dosages, it was decreased (25).…”
Section: Introductionmentioning
confidence: 92%